The Relationship between Neural Properties, Mechanical Properties,Functional Outcomes, and Clinical Parameters in Spastic Chronic Stroke Patients: An Observational Study - Ehsan Ghasemi; Khosro Khademi-Kalantari; Fateme Bokaee; Alireza Akbarzadeh Baghban; Majid Ghasemi (Shiraz University of Medical Sciences, 2022)
Background: Subsequent to spasticity, which is a positive impairment of stroke,neural and mechanical changes often occur in paretic muscles, affecting muscle function. The aim of this study was to find more accurate indices, which could affect decisions about spasticity treatment by investigating the relationships among neural, mechanical, functional outcomes, and clinical parameters in spastic chronic stroke patients.Methods: This cross-sectional study investigated 45 spastic chronic stroke patients. Clinical assessments were conducted using the Modified Modified Ashworth Scale (MMAS). Neural properties including H-reflex latency and Hmax/Mmax ratio were acquired. Mechanical properties including fascicle length,pennation angle, and thickness of spastic medial gastrocnemius muscle were evaluated. Functional outcomes were evaluated by the Timed Up and Go (TUG) test and Timed 10-Meter Walk Test (10-m WTT). Spearman's rank correlation analysis in SPSS version 22.0 was used to find correlations between parameters.Results:A low negative correlation was determined between MMAS and H-reflex latency (r=-0.320, P=0.032). MMAS score had a low significant relationship with pennation angle (r=0.296, P=0.049) and thickness of muscles (r=0.389,P=0.008). However, no significant correlation was found between MMAS and functional outcomes.Conclusion:Based on these findings, it is clear MMAS can partly identify changes in neural and mechanical properties of spastic muscles.